PENILAIAN WISATAWAN TERHADAP POTENSI WISATA DANAU PLTA KOTO PANJANG KAB. KAMPAR - Rahmat Hidayat; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tourism Potential is every that can be utilized as an ability and needed for business and tourism develoopment, so as to increase tourist arrivals in the tourist attraction. The reseacrh aims to determine tourist of rating in The PLTA lake Koto Panjang Kampar Regency .This study used a descriptive quantitative method to examine problems in the lift. The samples in this study were 100 respondents, who were taken by using accidental sampling. While data collection techniques in this study using observation, questioner, and interviews. By using a Likert scale as a measure to determine the length of the short interval. With sub-variables on tourism potential (Spillane, 2018) is divided into Rowing the boat, Fishing, Camping, Homestay, Restaurant, Transportation, Road Conditions,  Worship Place, Parking Area.From the results of research conducted in the field of research on the tourist rating in PLTA lake Koto Panjang Kampar Regency the category good.  Keywords : Tourism Potential, Tourist Rating.